Financial relationships between industry and principal investigators of US cooperative group randomized cancer clinical trials. Issue 9 (23rd July 2021) - Metzger, April L.; Kusi Appiah, Adams; Wright, Christopher M.; Jairam, Vikram; Amini, Arya; Park, Henry S.; Welsh, James W.; Thomas, Charles R.; Verma, Vivek; Ludmir, Ethan B.
Abstract: Financial conflicts of interest (FCOIs) could bias the potentially practice‐changing oncologic randomized clinical trials (RCTs) of tomorrow. This investigation characterized the FCOIs of the principal investigators (PIs) of all currently accruing trials of the four (adult) cooperative groups of the National Clinical Trials Network. For our study, the PI list was first compiled, and each name was then searched in the CMS Open Payments database. For each transaction (general payments (GPs) or research funding (RF)), the amount/number/source of payments was recorded. Results showed that from 2014 to 2019, the 91 PIs collectively accepted nearly one‐third of a billion dollars ($10 477 023 GPs and $320 096 233 RF). The mean and median GP was $6505 and $945, respectively, and $301 693 and $49 824 RF, respectively. Multivariable Gamma regression analysis revealed that higher GP sums were associated with RCTs involving any type of systemic therapy, and higher RF sums with medical oncologist PIs, trials with phase III components, and RCTs involving radiotherapy ( P  < .05 for all). Both higher‐volume GPs and RF were predicted by PIs having accepted payment(s) from the manufacturer of the drug utilized in their RCT ( P  < .001 GP, P  = .008 RF). Taken together, the main message of this investigation is that FCOIs may be particularly high in PIs of phase III systemic therapy trials, especially if the PI accepted payments from the manufacturer of the drug utilized in their trial. Such RCTs should be thoroughly scrutinized by medical journals, the FDA, and insurance companies for potential "industry bias" that could influence the integrity of their conclusions.